Co-Existence of Tuberculosis and Lung Cancer - Aribowo, Kornelis; Medison, Irvan; Mizarti, Dessy; Fitrina, Dewi Wahyu (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Tuberculosis (TB) and lung cancer cause significant morbidity and mortality worldwide and pose a global health threat. Each year these two diseases account for more than 1.6 million deaths worldwide. The incidence of both diseases is still high in many developing countries, especially in Asian countries. TB and lung cancer are often confused and misdiagnosed, especially in countries with diagnostic challenges of low TB incidence and risk of missed diagnosis.Case Presentation: The following is a case report of a 53-year-old male patient diagnosed with pulmonary TB accompanied by right lung cancer, and the same respiratory complaints can be had by lung cancer and TB. However, the presence of facial edema (part of the superior vena cava syndrome) causes clinicians to focus more on lung cancer so that the diagnosis of TB is often overlooked.Conclusion: Tuberculosis should be a significant concern, especially in patients with malignancies such as lung cancer and located in TB endemic areas. Delay in diagnosis and or miss diagnosis will affect the patient's outcome.